Corrosion of iron, nickel and aluminium in deep eutectic solvents. (20th November 2021) - Ahmed, Essa I.; Ryder, Karl S.; Abbott, Andrew P.
Abstract: Deep eutectic solvents (DESs) are mixtures of quaternary ammonium halides with hydrogen bond donors and are increasingly being used in applications where they are in contact with metals. This study investigates the corrosion of iron, nickel and aluminium in DESs. It shows that none of the metals show significant corrosion when glycerol is used as a hydrogen bond donor but when an acidic hydrogen bond donor such as oxalic acid is used, both iron and aluminium show catastrophic corrosion as may be expected. Surprisingly, however, nickel does not corrode in the acidic DES, Oxaline. The differences in corrosion observed for aluminium and iron are explained in terms of passivating films and the slowness of the oxygen reduction reaction despite the relatively high gas solubility. The high chloride ion content (roughly 4 mol dm −3 ) has a relatively small effect on the corrosion of the three metals. The formation of a passive layer as a result of hydrogen bond donor-metal ion complexes is shown to be more important. It is proposed that the low corrosion rates of some metals resulted from the slow rate of the cathodic reaction resulting from the high viscosity, low activity of water and low proton mobility. Graphical abstract: Image, graphical abstract